Self-reported awareness and attitude of cancer patients towards clinical nurse coordinators - Deeb, Ahmad (2017)
Background and objective: Lack of knowledge or poor perception towards the roles and responsibilities of clinical nurse coordinators among cancer patients might lead to a decrease in seeking their services. The objective of the study was to assess the knowledge, perception and attitude towards clinical nurse coordinators among cancer patients at a specialized cancer center in Jordan. Methods: This is a cross sectional study that was conducted by distributing a self-reported and anonymous survey to 240 cancer patients visiting the center. The survey questioned some patient characteristics such as sex, age, educational level, marital status, disease type and duration, type of therapy. The patients’ knowledge (12 statement), the perception (9-statement) regarding the actual roles/responsibilities of coordinators and the attitude (5 statement) towards seeking their services were measured. Responses on Likert scales were converted to percentage mean scores. Results: The overall percentage mean scores ± standard deviation of knowledge was 59 ± 17, perception towards clinical nurse coordinators (79 ± 14) and attitude towards seeking their services (69 ± 16). Linear regression showed that participants on chemotherapy had significantly better perception (higher scores) compared to participants on concurrent therapies (β = -3.91, p = .049). Participants with higher knowledge scores had better perception indicating a better comprehension about the clinical nurse coordinators’ roles, compared to those with lower knowledge percentage mean scores (β = 0.13, p = .019). Female patients had higher percentage mean score of attitude compared to male particpants (β = -3.77, p = .034). Better perception of Clinical nurse coordinators (CNCs) among cancer patients was significantly more associated with a more positive attitude towards seeking CNC services (β = 0.72, p < .001). Conclusions: Patients’ knowledge about the roles and responsibilities of nurse coordinators is associated with a better patients’ perception towards coordinators, which in return is associated with a more positive attitude towards seeking their services. Special consideration should be paid for patients on concurrent therapies who were more likely to have poorer perception towards clinical care coordinators compared to patients on chemotherapy. In addition, coordinators are expected to observe a more negative attitude towards seeking their services among male cancer patients.